Kinerja Anggota Legislatif Perempuan Provinsi Sumatera Utara Dalam Merespon Kepentingan Perempuan - Mikha Juni Adelina Mendrofa; Beby Masitho Batubara; Yurial Arief Lubis (Universitas Medan Area, 2021)
Issues on gender issues are issues that have long existed both in Indonesia and in other countries, in essence gender issues are issues that demand equality between men and women, this is actually the right of every citizen because both the people men and women are one and the same citizen and protected by the state constitution. The purpose of the study is to refer to things that are to be achieved in a study. The goal to be achieved is to know the performance of female members in the North Sumatra provincial DPRD and find out what factors hinder the performance of female members of the DPRD North Sumatra Province. The research method used in this study is a qualitative research method. The performance of women legislative members in carrying out their duties and authority can be seen in this period in achieving superiority or fighting for women's rights In the DPRD of North Sumatra Province it is quite good.